DETERMINANTS OF PROFIT GROWTH IN SHARIA BANKING COMPANIES IN INDONESIA - Maya Sari; Maysarah Nabila; Jufrizen Jufrizen (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine whether company size affects profit growth in Sharia banking companies, to find out whether NPF (Non Performing Financing) affects profit growth in Sharia banking companies to determine whether company size, NPF (Non Performing Financing) affects growth profit in Sharia banking companies. In this study, the author uses the nature of research with quantitative data, quantitative data is data in the form of numbers or data that is numbered. The results obtained are for the size of the company obtained tcount 6.637. Because tcount (6.637) ttable (1.672) then Ha is rejected so that it can be concluded that company size has a partial effect on profit growth. For NPF obtained tcount 2.203. Because tcount (2.203) ttable (1.672) then Ha is accepted so that it can be concluded that NPF has a partial effect on profit growth. From the results of the regression test using SPSS 18.0. The value of the coefficient of determination is 0.462, indicating that profit growth is influenced by firm size and NPF of 46.2%, while the rest is influenced by other variables/factors not included in this study..Keywords: Company Size, Non Performing Financial, Profit Growth